Between Opportunities And Challenges: Analysis Of Factors Triggering The Emergence Of New Secondary Schools In Jayapura City - Ramandei, Lazarus; Rorrong D, Semuel (STEBIS Bina Mandiri, 2025)
The zoning system implementation since 2017 has significantly transformed secondary education landscape in Jayapura City, triggering emergence of new secondary schools. This study analyzes factors driving new secondary schools proliferation during zoning era and identifies accompanying opportunities and challenges. Using qualitative approach with case study method, research involved 35 key informants including education providers, local government, and community, plus analysis of licensing documents and education statistics (2017-2024). Results show significant increase from 68 schools (2017) to 89 schools (2024), representing 30.9% growth. Main triggering factors include limited existing school capacity, profitable education business opportunities, geographical equity demands, and upper-middle class resistance to zoning restrictions. Opportunities include equitable education access, program diversification, and increased infrastructure investment. Challenges encompass quality disparities, system fragmentation, and operational sustainability concerns.